Smart luminescent molecular europium complexes and their versatile applications. Issue 20 (12th May 2021) - Devi, Rachna; Rajendran, Marikumar; Singh, Kasturi; Pal, Raksha; Vaidyanathan, Sivakumar
Abstract : A series of smart luminescent Eu(iii ) complexes (C1 = Eu(DBM)3 ligand 1, C2 = Eu(DBM)3 ligand 2, C3 = Eu(DBM)3 ligand 3, C4 = Eu(DBM)3 ligand 4, C5 = Eu(DBM)3 ligand 5) were synthesized by using C1-functionalized phenanthro-imidazole derivatives as the neutral ligands and dibenzoylmethanate (DBM) as the anionic ligand. Abstract : A series of smart luminescent Eu(iii ) complexes (C1 = Eu(DBM)3 ligand 1, C2 = Eu(DBM)3 ligand 2, C3 = Eu(DBM)3 ligand 3, C4 = Eu(DBM)3 ligand 4, C5 = Eu(DBM)3 ligand 5) were synthesized by using C1-functionalized phenanthro-imidazole derivatives as the neutral ligands and dibenzoylmethanate (DBM) as the anionic ligand. All the neutral ligands and their corresponding Eu(iii ) complexes were structurally characterized by spectroscopic methods. Photoluminescence (PL) emission spectra of the ligands showed blue to bluish-green emission, whereas their corresponding Eu complexes showed multi-color emission in solution and red emission in the solid state (solid as well as neat thin film). The energy transfer mechanism between the ligand and the Eu(iii ) ion is explained based on both theoretical (density functional theory (DFT) and time-dependent-DFT) and experimental study. Red light-emitting diodes (LEDs) were fabricated by integrating a near-ultraviolet (NUV)_ LED chip (∼395 nm) with Eu(III) complexes and all of the LEDs showed excellent color purity. A hybrid white LED was fabricated by conjugating the mixed phosphor dye (ligand and complex) with near UV LED, showing superior white light emission characteristics (CCT (5298), CRI (80%), CIE ( x = 0.337, y = 0.343)). In addition, dual emission Eu(iii ) complexes were explored for thermo-sensor (in the range 303–353 K) applications. Paper-based acid–base vapour sensors (exposure leads to a switch in the emission color (bluish-green to red)) using these complexes were explored and can also be used for anti-counterfeiting applications.